INFLUENCING CONSUMER’S BEHAVIOR: PERSPECTIVE OF INFORMATION QUALITY AND CONSUMERS REVIEWS ON AIRYROOMS - Kurnia, Gres; Sulistiani, Putri B (PEOPLE: International Journal of Social Sciences, 2019)
Related to the rapid development of technology, many business models have been changed. It emerges the new concept of business model including VHO (Virtual Hotel Operator). Virtual Hotel Operators emerges on 2015 especially in particular countries such as India. India is the first country that introducing the concept of Virtual Hotel Operators. This concept was developed well in Asia including Indonesia. In Indonesia, there is a company that adopted the concept of VHO called as AiryRooms. AiryRooms is the budget hotel management company that manage and promote the best hotel room in Indonesia by applying the standard of procedure based on its standards. This research is to examine the factors of the intention to buy on Airy Room using some key factors such as Review, and Information Quality. Structural equation model is used to test the relationship of these factors with Satisfaction, Perceived Value, and Purchase Intention. The result indicate that Information Quality and Consumers Reviews as the important precursors then Satisfaction and Perceived Value are the key determinants of purchase intention. By providing high-quality of information that is clear, timely, relevant, and easy to understand is essential to enhance the efficiency of searches, to increase customer’s satisfaction of the information, and to avoid information overload. Further studies are suggested to explore their comparison between respondents with and without experience using the Virtual Hotel Operator. The sampling method used in this study was adequately suited to its research purpose, the generalisability could be enhanced if future research systematically sampled from more diverse population.